SNP PADA GEN KEMOKIN C-C MOTIF LIGAN 7 (CCL7) PENDERITA STROKE DI KABUPATEN MANOKWARI - Simamora, Muti Dornita; Islam , Muhammad Fajar; Taher, Achmad (FMIPA Universitas Papua, 2023)
Chemokines are key components in the development of chronic disease. Chemokine C-C motif ligan 7 (CCL7) is one of the chemokines believed to be associated with the pathology of atherosclerosis that causes stroke. CCL7 may play a role in inflammatory events by attracting macrophages and moncytes to further amplify inflammatory processes and contribute to atherosclerosis progression. Common Genetic variation in CCL7 gene has been associated with atherosclerosis progress, so the main objective of this study was identification of polymorphism of CCL7 gene in stroke patients. Five blood samples were taken from five patients suffering from stroke. The DNA of the blood samples were extracted, amplified its CCL7 gene, and sequenced. The results showed a sequence of 1151 bp consisting of regulator, exon 1, intron and exon 2. One polymorphic sites were found in the intron 1 region, at position 1447. The SNP genotype identified was TC.